Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.1 Inverse Functions - 6.1 Exercises - Page 407: 43



Work Step by Step

Since $f(4)=5$, this implies $f^{-1}(5)=4$ and so, by theorem 7, $(f^{-1})'(5)=\frac{1}{f'(f^{-1}(5))}=\frac{1}{f'(4)}=\frac{3}{2}.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.